Ascocoryne turficola (Fungi, Ascomycetes), a species new to Poland - Małgorzata Stasińska (Acta Societatis Botanicorum Poloniae, 2011)
Ascocoryne turficola, one of the rarest fungi in Europe, has been recorded for the first time in Poland. Its distribution presented on the map, ecological notes and morphology of ascocarps are based on the authors' own material.